Understanding the active role of water in laboratory chamber studies of reactions of the OH radical with alcohols of atmospheric relevance - Garavagno, María de los A. (2024)
This is an Accepted Manuscript, which has been through the Royal Society of Chemistry peer review process and has been accepted for publication. Accepted Manuscripts are published online shortly after acceptance, before technical editing, formatting and proof reading. Using this free service, authors can make their results available to the community, in citable form, before we publish the edited article. We will replace this Accepted Manuscript with the edited and formatted Advance Article as soon as it is available. You can find more information about Accepted Manuscripts in the Information for Authors. Please note that technical editing may introduce minor changes to the text and/or graphics, which may alter content. The journal’s standard Terms & Conditions and the Ethical guidelines still apply. In no event shall the Royal Society of Chemistry be held responsible for any errors or omissions in this Accepted Manuscript or any consequences arising from the use of any information it contains. Enlace autora: https://www.researchgate.net/profile/Maria-De-Los-Angeles-Garavagno/publication/379517439_Understanding_the_active_role_of_water_on_laboratory_chamber_studies_of_reactions_of_the_OH_radical_with_alcohols_of_atmospheric_relevance/links/6613e2603d96c22bc77ae8a0/Understanding-the-active-role-of-water-on-laboratory-chamber-studies-of-reactions-of-the-OH-radical-with-alcohols-of-atmospheric-relevance.pdf